Association of Intra-individual Differences in Estimated GFR by Creatinine Versus Cystatin C With Incident Heart Failure - Chen, Debbie C; Shlipak, Michael G; Scherzer, Rebecca; Bansal, Nisha; Potok, O Alison; Rifkin, Dena E; Ix, Joachim H; Muiru, Anthony N; Hsu, Chi-Yuan; Estrella, Michelle M (American journal of kidney diseases, 2022)
Lower estimated glomerular filtration rate (eGFR) is associated with heart failure (HF) risk. However, eGFR based on cystatin C (eGFR ) and creatinine (eGFR ) may differ substantially within an individual. The clinical implications of these differences for risk of HF among persons with chronic kidney disease (CKD) are unknown. Prospective cohort study. 4,512 adults with CKD and without prevalent HF who enrolled in the Chronic Renal Insufficiency Cohort (CRIC) Study. Difference in GFR estimates (eGFR ; ie, eGFR minus eGFR ). Incident HF hospitalization. Fine-Gray proportional subhazards regression was used to investigate the associations of baseline, time-updated, and slope of eGFR with incident HF. Of 4,512 participants, one-third had eGFR and eGFR values that differed by over 15 mL/min/1.73 m . In multivariable-adjusted models, each 15 mL/min/1.73 m lower baseline eGFR was associated with higher risk of incident HF hospitalization (hazard ratio [HR], 1.20 [95% CI, 1.07-1.34]). In time-updated analyses, those with eGFR less than -15 mL/min/1.73 m had higher risk of incident HF hospitalization (HR, 1.99 [95% CI, 1.39-2.86]), and those with eGFR ≥15 mL/min/1.73 m had lower risk of incident HF hospitalization (HR, 0.67 [95% CI, 0.49-0.91]) compared with participants with similar eGFR and eGFR . Participants with faster declines in eGFR relative to eGFR had higher risk of incident HF (HR, 1.49 [95% CI, 1.19-1.85]) compared with those in whom eGFR and eGFR declined in parallel. Entry into the CRIC Study was determined by eGFR , which constrained the range of baseline eGFR -but not eGFR -values. Among persons with CKD who have large differences between eGFR and eGFR , risk for incident HF is more strongly associated with eGFR . Diverging slopes between eGFR and eGFR over time are also independently associated with risk of incident HF.